Educators’ perceptions and challenges of student assessment process at Prince Sattam Bin Abdulaziz University dentistry program: a qualitative study - Abdullah Saad Alqahtani; Sami Al-Nasser; Abdullah Alzahem; Nasser Raqe Alqhtani (BMC Medical Education)
Abstract Background As part of Saudi Vision 2030, there is increasing demand for dentistry colleges to provide training in the student assessment process. Assessment is the process of accurately determining a learner’s skills across multiple educational domains. The objectives of this study were to investigate teachers’ perspectives, assessment challenges, and make recommendations for improving the assessment process of undergraduate dental students at Prince Sattam bin Abdulaziz University in Al-Kharj, Saudi Arabia. Methods A qualitative study employed the grounded theory approach following purposive sampling. Four focus group interviews were conducted with course directors from the College of Dentistry at Prince Sattam bin Abdulaziz University (PSAU) using open-ended questions for data collection. Otter software was used for the transcription and NVivo 14 for the data analysis. Results Four themes emerged: perspectives on the assessment process, summative and formative assessments, challenges of assessments, and proposed solutions to the assessment challenges. Most educators perceived assessments as assessments of learning, with the planning and execution of assessments requiring regulation. Different feedback models were occasionally used by examiners to improve student performance. Examiner standardization training, communication, and calibration were lacking, according to the educators in this study. Conclusion The challenges of the assessment process in the College of Dentistry at PSAU are multifactorial including the examiners themselves, students, and the college. These challenges indicated the need for a tailor-made, appropriately designed faculty development training program related to different methods of student assessment.